Co-opetition dalam Pengelolaan Bisnis Pariwisata di Indonesia (Proceeding Fakultas Ekonomi, 2011)
This article intended to explain about the concept of co-operation and competition in the tourism industry. Because of the tourism business has the characteristics of interdependent requires to can not be avoid from cooperation at the same time despite having to compete with one another. Therefore, in managing the tourism businesses need a strong basis of collaboration is a positive businessmen conduct, and has a strategic resources/strategic assets which greatly benefits of each business so that the intensity of cooperation that is built to support the creation of synergy between organizations. Competition is raised is how every business can create a unique and